고성능 콤팩트형 AC모터드라이브 고조파 필터 제안 - 박병주(Byung-Ju Park); 윤동철(Dong-Chul Yoon); 오정철(Jeong-Cheol Oh); 배병열(Byung-Yeol Bae); 황안일(An-Il Hwang); 유항규(Hang-Kyu Yoo); 최석근(Seok-Keun Choi) (전기학회 논문지 P권, 67(4), 2018)
The harmonic reduction method of ac motor drive, ACL and DCL were commonly used, but the current distortion ratio was only 35%, thus the several different types of filters as BBHF(broad band harmonic filter), HHF(hybrid harmonic filter), NHHF(new hybrid harmonic filter) have been developed to satisfy the IEEE Std. 519 harmonic limitation. However, these filters had been limited marketability due to cost and size problems. This study suggests the methods to reduce cost and size of the harmonic filter including topologies, besides we discussed simulation results of the power system with regard to the implementation and performance of the filters.